Multiple abnormalities in permanent maxillary incisors following trauma to the primary dentition - Nitesh Tewari; Ramesh Kumar Pandey (Wolters Kluwer Medknow Publications, 2011)
Diverse consequences to the trauma to primary dentition are sometimes difficult to explain. This report describes a rare case of sequelae to primary tooth trauma. The traumatic episode which occurred at the age of 3 years resulted in abnormally large crowns of 11 and 21 with yellowish-brown discoloration and enamel hyperplasia. It also led to dilaceration in the root of 21 and enamel hypoplasia with discoloration in 12 and 22.